Helping and Antisocial Behavior in the Workplace - Michael Haylock; Patrick Kampkötter; Michael Kosfeld; Ferdinand von Siemens (Institute of Labor Economics (IZA), 2023)
We offer a comprehensive analysis of the organizational and behavioral foundations of employees' helping and antisocial behavior as an integral part of a firm's workplace culture and working climate. Using representative employer-employee panel data of larger German private-sector firms, we document a large variation in helping and antisocial behavior across firms. Our regression results show that differences in supervisors' people skills, as well as workforce trust, social preferences, and personality traits explain these firm-level differences in helping and antisocial behavior in the workplace. Our measures are derived from established survey constructs and include preference items that have been behaviorally validated in experimental games by prior research. Together, the results corroborate the importance of both leadership quality and workforce composition for the manifestation of helpful and hostile workplace cultures.
Keywords: D01; M14; M21; M50; 330; helping; antisocial behavior; leadership; social preferences; trust; personality; human resource management practices